Expression Patterns of the Neuropeptide Urocortin 3 and Its Receptor CRFR2 in the Mouse Central Auditory System - Pagella, Sara; Deussing, Jan M.; Kopp-Scheinpflug, Conny (Frontiers in Neural Circuits, 2021)
Sensory systems have to be malleable to context-dependent modulations occurring over different time scales, in order to serve their evolutionary function of informing about the external world while also eliciting survival-promoting behaviors. Stress is a major context-dependent signal that can have fast and delayed effects on sensory systems, especially on the auditory system. Urocortin 3 (UCN3) is a member of the corticotropin-releasing factor family. As a neuropeptide, UCN3 regulates synaptic activity much faster than the classic steroid hormones of the hypothalamic-pituitary-adrenal axis. Moreover, due to the lack of synaptic re-uptake mechanisms, UCN3 can have more long-lasting and far-reaching effects. To date, a modest number of studies have reported the presence of UCN3 or its receptor CRFR2 in the auditory system, particularly in the cochlea and the superior olivary complex, and have highlighted the importance of this stress neuropeptide for protecting auditory function. However, a comprehensive map of all neurons synthesizing UCN3 or CRFR2 within the auditory pathway is lacking. Here, we utilize two reporter mouse lines to elucidate the expression patterns of UCN3 and CRFR2 in the auditory system. Additional immunolabelling enables further characterization of the neurons that synthesize UCN3 or CRFR2. Surprisingly, our results indicate that within the auditory system, UCN3 is expressed predominantly in principal cells, whereas CRFR2 expression is strongest in non-principal, presumably multisensory, cell types. Based on the presence or absence of overlap between UCN3 and CRFR2 labelling, our data suggest unusual modes of neuromodulation by UCN3, involving volume transmission and autocrine signaling.